Lexical diversity in Spanish as a second language students’ speech (level C1) - Guillén Solano, Patricia (2020)
In this article lexical diversity in Spanish as a foreign language spoken discourse of C1 level students is analyzed. By applying the formula Pd50, the index of lexical diversity is calculated on the basis of five oral presentations within a university setting. According to the results, and considering some complementary qualitative factors, lexical diversity is analyzed taking into account the descriptors for lexical competence established by the Marco Común Europeo de Referencia para las lenguas (2002) and the Plan Curricular del Instituto Cervantes (2006). From this analysis it is concluded that the lexical diversity of the oral presentations does not meet those descriptors, while possible reasons for this inconsistency are proposed. Finally, the relationship between lexical diversity and lack of competence in discourse genres in educational settings is discussed.